2018
DOI: 10.1273/cbij.18.32
|View full text |Cite
|
Sign up to set email alerts
|

<b>Specific interactions between vitamin D receptor and ligand depending on its chirality: </b><i><b>ab initio</b></i><b> fragment molecular orbital calculations</b>

Abstract: The chirality of a compound affects its biochemical and pharmaceutical properties. It was found that the binding affinity between vitamin D receptor (VDR) and its ligand depends significantly on the chirality of the ligand. To elucidate the reason for this dependence, we here investigated the specific interactions between VDR and two types of ligands with different chirality, using ab initio fragment molecular orbital (FMO) calculations. The FMO results reveal that the part of ligand with different chirality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…As an alternative to manual preprocessing, an automated preprocessing approach was also initiated by the development working group of the FMODD reported as Auto-FMO protocol (Figure ). As reported from many previous studies, ,,,, ,, if only a small number of biopolymers are to be subjected to FMO calculation, manual processing using visual inspection and trial and error can be conducted. However, the manual approach is not practical for anything more than a few hundred complexes of drug target proteins and certainly not for the more than 160 000 experimental structures registered in the PDB, so an automatic pretreatment protocol, which was named as Auto-FMO protocol (Figure ), was developed with pipeline pilot .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to manual preprocessing, an automated preprocessing approach was also initiated by the development working group of the FMODD reported as Auto-FMO protocol (Figure ). As reported from many previous studies, ,,,, ,, if only a small number of biopolymers are to be subjected to FMO calculation, manual processing using visual inspection and trial and error can be conducted. However, the manual approach is not practical for anything more than a few hundred complexes of drug target proteins and certainly not for the more than 160 000 experimental structures registered in the PDB, so an automatic pretreatment protocol, which was named as Auto-FMO protocol (Figure ), was developed with pipeline pilot .…”
Section: Methodsmentioning
confidence: 99%
“…We and newly calculated and collected more than 13 600 FMO calculation data sets ,, including data sets for 1418 unique PDB entries in collaboration with the FMO Drug Design Consortium (FMODD), which was established for the application of computational science such as FMO calculation to drug discovery. Using these data, we constructed the FMODB, which is a treasure trove of quantitative inter- and intramolecular interaction energies in biomolecular systems that will be useful for a wide range of applications in many life science research fields related to drug discovery and structural biology, including the study of molecular recognition.…”
Section: Introductionmentioning
confidence: 99%
“…We discussed the modeling conditions for the complementation of heavy atoms, with/without water molecules, and the restraint of heavy atoms on the minimization in the FMODD consortium. As a result, some modeling case studies have been reported [28][29][30][31][32][33][34]. Another issue is the treatment of a large amount of structure data, including more than 145,000 protein data bank (PDB) entries, to construct an FMO database [35] in the future.…”
Section: Introductionmentioning
confidence: 99%